Infection with Strongyle in Bali Cattle (Bos sondaicus) in Kupang Regency: Infeksi Cacing Strongil pada Sapi Bali (Bos sondaicus) di Kabupaten Kupang - Winarso, Aji; Mbula, Viktoriano Kingking Dalman; Sanam, Maxs Urias Ebenheizer (Veterinary Biomedical and Clinical Journal, 2022)
Gastrointestinal parasitic worm infection is one of the most common disease agents found in Bali cattle.The large number of eggs found, indicates the prevalence of nematodiasis in a region. This study aims tocalculate the prevalence and analyze the relationship of the degree of infection with risk factors for theincidence of gastrointestinal nematodiasis in Bali cattle in Kupang Regency. This study uses acrosssectionalstudy with simple random sampling and the number of samples taken is 171 samples.Microscopic examination of faecal samples uses the McMaster method to identify gastrointestinalnematode eggs based on their type. Data analysis uses the Chi-Square test to determine the relationshipofthe significance of risk factors. Based on the results of research, Strongyle type nematodes have aprevalence value of 46.78%. Age and sex did not show an influence on infection risk.